Managing beef genotypes for profit: a computer simulation - Schalles, R.R.; Martin, L.C.; Zoellner, K.O. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In a computer simulation based on KSU data, cattle bred and managed to be moved directly from weaning to feedlot and slaughtered at a young age produced the greatest profit. Cattle that were too small or too large and management systems that increased age at slaughter were less profitable. This accelerated system of production allows a producer to take advantage of superior genetics and the economic opportunities they provide, especially with retained ownership. The beef industry has the opportunity to continue to produce quality beef, while reducing days to slaughter by taking advantage of the higher efficiency of feed conversion of younger animals. In addition, less shrink, lower trucking costs, fewer sick days, a reduction in medication, lower marketing costs, and reduced interest costs are associated with the accelerated production system. With the availability of EPDs, there is little reason for profit minded cow-calf producers to wean calves that are not of acceptable size to enter the feedlot after the weaning process.
Keywords: Beef; Beef genotype-management interactions; Economics; Simulation